Study of feto maternal outcome of teenage pregnancy at tertiary care hospital - D., Rita; Naik, Kiran; Desai, R. M.; Tungal, Sphurti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Teenage pregnancy due to changing social conditions, it’s important to study the implications of the maternal and fetal health. It is a serious health problem, more so in developing countries like India. Young mothers and newborns are at increased risk of anaemia, pre-eclampsia, increased rate of LSCS, PTVD, LBW, prematurity, NICU care, RDS, sepsis, IUGR. Hence, study is directed to identify the problems and their outcome. Methods: Teenage pregnant ladies between 18 to 20 years were taken up for the study. Study duration was 1 year from January to December 2016, at SDM Medical College Dharwad. During this period, all cases were included in the study, irrespective of their booking and unbooking statuses after 28 weeks of pregnancy are taken. Results: Study showed the incidence of teenage pregnancy is 10.26%. 79.2% of teenage mothers have varying grades of anaemia, 13.6% of women had eclampsia, 16.01% had preterm deliveries, LSCS rate were as high as 52%, 17.4% had instrumental deliveries, 12.5% were low birth weight neonates, 8.4% requiring NICU care and 2% were perinatal deaths due to prematurity, respiratory distress, sepsis. Conclusions: As teenage pregnancy is associated with high risk of anaemia, pre-eclampsia, eclampsia, PTVD, instrumental delivery, high rate of LSCS, prematurity, low birth weight, perinatal death. It’s important to reduce the teenage pregnancy by improving the socio-economic condition, education, public awareness, strict implementation of law, good ANC care, nutrition, access to contraceptive services, sex education.